HUKUM PERKAWINAN MUSLIM DI BRUNEI DARUSSALAM (STUDI ANALISIS MASLAHAT AT-THUFI) - Fitrianoor, Wahyu (Program Studi Hukum Keluarga Islam STAI Al-Falah Banjarbaru, 2023)
AbstractBrunei is claimed to be the oldest Malay kingdom in Southeast Asia. In addition, Brunei Darussalam is the only country in the Southeast Asian region that enforces Islamic criminal law, especially in civil matters Brunei has a long history, since the British position on their land. Various ways of diplomacy or politics are taken by Brunei to make Islamic civil law have power in the country.In the matter of marriage, the law adopted is a collaboration between customary law and Islamic law, although Islamic law is more pronounced in it. Therefore, in Brunei Islamic law in marriage starts from the election of guardians from the government, rules for recording marriages, polygamy, divorce, divorce claims, and even engagement issues. It does not stop there, Brunei also imposes criminal sanctions for violators of their marriage law.The benefits in Brunei law can be seen from the balanced accommodation of culture and Islamic law, this is because Brunei sees family law as an ijtihadiyah issue that must be decided with benefit, such as khitbah sanctions, appointment of Hakam, Kadi selection and criminal sanctions in family law.Keyword: Brunei, Marriage Law, Maslahat.AbstrakNegara Brunei diklaim adalah kerajaan melayu tertua di Asia Tenggara. Selain itu Brunei Darussalam adalah satu-satunya negara di kawasan Asia Tenggara yang memberlakukan hukum pidana Islam, terlebih dalam masalah perdata Brunei mempunyai sejarah panjang, sejak kedudukan Inggris atas tanah mereka. Berbagai cara diplomasi atau pun politik ditempuh Brunei hingga menjadikan hukum perdata Islam mempunyai kekuatan di negaranya.Dalam masalah perkawinan, hukum yang dianut adalah kolaborasi antara hukum adat dengan hukum Islam, walau hukum Islam lebih terasa di dalamnya. Oleh karena itu di Brunei hukum Islam dalam perkawinan dimulai dari pemilihan wali dari pemerintah, aturan pencatatan pernikahan, poligami, talak, gugatan cerai, bahkan masalah pertunangan. Tidak berhenti di situ, Brunei juga memberlakukan sanksi pidana untuk pelanggar undang-undang perkawinan mereka.Maslahat dalam hukum Brunei dapat dilihat dari pengakomorian budaya serta hukum Islam yang seimbang hal ini karena Brunei melihat hukum keluarga sebagai permasalah ijtihadiyah yang harus diputuskan dengan maslahat, seperti sanksi khitbah, penujukkan Hakam, pemilihan Kadi dan sanksi pidana dalam hukum keluarga.Kata Kunci: Brunei, Hukum Perkawinan, Maslahat